Kajian Filosofis Materi Pendidikan Akhlak Ibnu Miskawaih - Abdal Chaqil Harimi; Maragustam Siregar; Usman (Rayah Al-Islam, 2025)
Globalization is an inevitability that cannot be avoided by humans living in this era. The effects of globalization can be both positive and negative. An example of a positive effect that can be enjoyed by society is the rapid advancement of technology. In addition, they will be able to obtain information very quickly. However, if society is not ready, many negative effects will arise, one of which is a decline in morals and ethics. Therefore, this article attempts to offer a philosophical study related to moral education according to Ibn Miskawaih, which hopefully can answer contemporary educational challenges, especially those related to moral education. The author chose a qualitative approach with the type of Library Research using the book Primer Tahdzbul Akhlak (Primer on Moral Education) in its translated version and the book Filsafat pendidikan Islam membentuk Pendidikan Karakter (Islamic Philosophy of Education Shapes Character Education) by Prof. Dr. H. Maragustam Siregar, M.A., combined with other secondary sources. The results of the study explain that Ibn Miskawaih's thoughts on moral education were influenced by Greek philosophy, the Buwaih Dynasty period, and Islamic religious foundations. Furthermore, Ibn Miskawaih's educational model tends to optimize reason based on Islamic religious studies (foundations) in the process of forming Islamic morals. Meanwhile, the moral education material offered is the Middle Path, namely Qona'ah, Syaja'ah, Hikmah, Iffah, and 'Adalah.